Circular economy solutions to close water, energy and food loops in West Africa - International Water Management Institute (International Water Management Institute, 2021)
In West Africa, rapid urbanization and poor sanitation infrastructure are driving the spread of untreated fecal sludge and wastewater, contaminating water sources and increasing public health risks. With wastewater generation ranging from 20–150 liters per capita per day, circular economy approaches are urgently needed to recover resources and reduce environmental burdens. Innovative solutions piloted in Ghana demonstrate how waste can be transformed into value. In Kumasi, wastewater-fed aquaculture combined with vegetable farming through aquaponics has helped cover 60% of plant operating costs. In Accra, fecal sludge is co-composted with market waste to produce Fortifer™, an organic fertilizer certified for agricultural use. A second facility now processes 5,000 m³ of sludge and 300 tons of organic waste annually. Additionally, a briquette plant converts sawdust and rice husks into low-cost fuel for households and small industries. These models are supported by public-private partnerships and informed by IWMI’s research on risk mitigation, business models, and resource recovery.Scaling these solutions requires strengthened policy, institutional capacity, and financing mechanisms. By closing water, food, and energy loops, circular economy strategies improve sanitation, create jobs, and support climate-resilient urban systems across the region.